Conductive Transparent TiNx/TiO2 Hybrid Films Deposited on Plastics in Air Using Atmospheric Plasma Processing. (28th January 2014) - Dong, Siming; Watanabe, Makoto; Dauskardt, Reinhold H.
<x xml:space="preserve">Abstract</x> The successful deposition of conductive transparent TiNx/TiO2 hybrid films on both polycarbonate and silicon substrates from a titanium ethoxide precursor is demonstrated in air using atmospheric plasma processing equipped with a high‐temperature precursor delivery system. The hybrid film chemical composition, deposition rates, optical and electrical properties along with the adhesion energy to the polycarbonate substrate are investigated as a function of plasma power and plasma gas composition. The film is a hybrid of amorphous and crystalline rutile titanium oxide phases and amorphous titanium nitride that depend on the processing conditions. The visible transmittance increases from 71% to 83% with decreasing plasma power and increasing nitrogen content of the plasma gas. The film resistivity is in the range of ∼8.5 × 101 to 2.4 × 105 ohm cm. The adhesion energy to the polycarbonate substrate varies from ∼1.2 to 8.5 J/m2 with increasing plasma power and decreasing plasma gas nitrogen content. Finally, annealing the film or introducing hydrogen to the primary plasma gas significantly affects the composition and decreases thin‐film resistivity.